THE PERCEPTIONS OF INDONESIAN JUDGES IN SENTENCING MINOR DRUG OFFENDERS: CHALLENGES AND OPPORTUNITIES - Mustafa, Cecep (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
This paper presents the perceptions of Indonesian Judges in sentencing minor drug offenders. The judge holds a central role in the sentencing process, and because of the judicial discretion they can use it is essential to understand how judges come to their sentencing decisions. To develop an understanding of how judges perceive their actions in decision-making and sentencing of drug users, a total of 31 participants were interviewed. The data demonstrated that the majority of minor drug offenders are from poorer backgrounds. Poverty was found to lead people to the drug culture. Moreover, lack of understanding of the harm caused by taking drugs and living under drug prohibition were considered as contributing factors to people involved in minor drug offences. Thus, minor drug offenders are considered by judges as victims of their circumstances. Within structural inequality, the imposition of harsh sentencing to minor drug offenders who suffer from socio-economic problems raises issues surrounding justice. Within the current legal structure of Indonesian courts, which are primarily retributive and have drug prohibitionist policies, the majority of participating judges consider drug sentencing as reflecting those prohibitionist policies. However, a substantial minority of participating judges interpreted the form of the sentence within available limits. These findings will contribute to the sociological understanding of the context in which judicial culture shaped the formation of the judiciary as a group and the impact of Islamic culture on the participating judge’s positive preference for rehabilitative problem-solving in the Indonesian context.